WOMAN ENTREPRENEURSHIP THROUGH SHGs IN TAMIL NADU, INDIA - Revathi Pandian; P.Raja Raja; N.Mahesh Mahesh (Jurnal Ilmiah Ekonomi Bisnis, 2012)
Entrepreneurship development and income generating activities are a feasible solution for empowering women. It generates income and also provides flexible working hours according to the needs of home makers. Economic independence is the need of the hour. Participation in income generating activities helps in the overall empowerment of women. Empowering women through education, ideas, consciousness, mobilization and participatory approach can enable them to take their own decisions, make them self-reliant and self-confident. Past experience and network, correct business location, environment protection, less mistakes and orientation and training are positively influencing the business income of the women entrepreneurs. There are six independent groups of constraints are extracted and these factor are grouped as market constraints, institutional constraints, planning constraints, uncertainty constraints, policy constraints and information constraints. The training programmes should include identification and selection of potential entrepreneurs, and their motivation into entrepreneurial career through provision training and other inputs necessary to set up entrepreneurial units through micro-financing. To improve this situation, the proper coordination mechanism and monitoring system should be formulated and implemented.   Keywords: Entrepreneurship, Self-Help Groups, Business Income, Growth Constraints